Mitigasi Gempa Mengurangi Korban dan Kehancuran Akibat Goncangan dan Tsunami - -, Sarwidi (Unisia, 2016)
More than 2/3 of Indonesian provinve tends and potentially toward earthquake. At those area earthquake can happen suddenly. Earthquake can imply disaster or tsunami. To avoid earthquake constitutes something absurd to do, but to prevent or to minimize its impact could be done. At advanced countries people have high consciousness regarding three general steps: before, at the time earthquake happens and after happening earthquake. Meanwhile at developing countries earthquake management be done anplanned so well, so the destruction of this more than those of advanced countries. In this sense, Indonesia should apply planned disaster management so well and consecutively.